1H NMR-based fingerprinting of eleven Mexican Capsicum annuum cultivars. (July 2019) - Florentino-Ramos, Elideth; Villa-Ruano, Nemesio; Hidalgo-Martínez, Diego; Ramírez-Meraz, Moisés; Méndez-Aguilar, Reinaldo; Velásquez-Valle, Rodolfo; Zepeda-Vallejo, L. Gerardo; Pérez-Hernández, Nury; Becerra-Martínez, Elvia
Abstract: Approximately 90% of the chili peppers consumed in the world are harvested in Mexico. The present article describes the untargeted 1 H NMR-based metabolomic profiling of 11 cultivars of Capsicum annuum species which are routinely consumed worldwide. The metabolomic fingerprinting detected via 1 H NMR contained 44 metabolites including sugars, amino acids, organic acids, polyphenolic acids and alcohols which were identified by comparison with the literature data, with Chenomx database and by 2D NMR. Statistical approaches based on principal component analysis (PCA) and linear discriminant analysis (LDA) were used to classify the Capsicum annuum cultivars according to their metabolite profile. LDA revealed metabolomic differences and similarities among Capsicum annuum cultivars, whereas hierarchical cluster analysis (HCA) significantly separated the cultivars according to the phylogenetic trees obtained. Substantial endogenous levels of free amino acids and carbohydrates were detected in all the studied cultivars but interestingly, Capsicum annuum cv. mirasol and C. annuum cv . chilaca contained almost three-fold more endogenous levels of vitamin C than the other cultivars. Considering that this antioxidant was found in crude aqueous extracts, its abundance could be directly proportional to its bioavailability for human nutrition. The results suggest that 1 H NMR is an effective method to determine differences among cultivars of the Capsicum annuum species. Graphical abstract: Unlabelled Image Highlights: The 1 H NMR metabolomics profiling of 11 cultivars of Capsicum annuum were compared. 1 H NMR metabolomics profiling revealed a particular fingerprinting to identify each cultivar. PCA and LDA models confirmed differences among the cultivars.